PENGARUH VARIASI TEMPERATUR INTERCRITICAL ANNEALING TERHADAP STRUKTUR MIKRO DAN KEKERASAN BAJA AISI 1020 DENGAN MEDIA PENDINGIN AIR GARAM - Syanur, Farid Nanda; Paundra, Fajar; Prasetyo, Richo (P3M Politeknik Negeri Indramayu, 2025)
The development of technology in enhancing the mechanical properties of materials, such as hardness in metals, has progressed rapidly, particularly in steel. Based on its carbon content, carbon steel is classified into three categories: high-carbon steel, medium-carbon steel, and low-carbon steel. Low-carbon steel contains carbon in the range of 0.04% to 0.30%, one of which is AISI 1020 steel. This study aims to determine the effect of varying intercritical annealing temperatures on the microstructure and hardness of AISI 1020 steel using a saltwater cooling medium. The heating process was conducted using a furnace for 3 hours at different temperatures of 673°C, 723°C, 773°C, 823°C and 873°C. The tests performed included microstructure analysis and hardness testing. The hardness test was conducted using a hardness tester with the Vickers method, while the microstructure analysis was carried out using a trinocular metallurgical microscope. The results showed that the formed phases remained the same as in the initial specimen, consisting of ferrite and pearlite. The highest hardness value was obtained from the specimen heated at 823°C, reaching 243.49 HVN, while the lowest hardness value of 184.33 HVN was recorded in the initial specimen without heat treatment.